The 7-step success system to building a - Rubino, Joe. (Wiley, 2005)
Millions of people around the world participate daily in network marketing sales. This book offers, for the first time, a step-by-step plan for building a profitable, long-lasting network marketing business. This simple, proven system—from an author who built his own million-dollar network marketing business—gives everyone in the network marketing industry the tools and tactics they need to succeed spectacularly. Rubino’s seven-step system covers every aspect of the network marketing business, from planning to prospecting to training, and gives you the confidence and attitude you need to make your business work and keep it profitable.